Comparative Assessment of Heavy Metals in Commercial and Domestic Cassava Flour in Oyo State, Nigeria - Olanrewaju John Adedayo; Campos Adedoyin Temiloluwa; Tairu Tajudeen T; Amoo Olakunle; Olabosoye Peter Oladeji; Adegbamike Emmanuel O; Awogbade Henry Adetayo; Alamu Sunday O (Public Health, 2026)
Heavy metal contamination of staple foods poses a significant public health risk in Nigeria, where traditional processing methods like roadside drying are prevalent. This study assessed the levels of heavy metal contamination in cassava flour (Manihot esculenta Crantz) processed and marketed in Oyo State. Samples were collected from three sources: a commercial outlet at Oja-Oba market, a roadside drying site along the Ido-Eruwa road, and a controlled self-dried batch from the Lead City area. The concentrations of Manganese (Mn), Iron (Fe), Copper (Cu), Zinc (Zn), Lead (Pb), Cadmium (Cd), Chromium (Cr), and Selenium (Se) were analyzed using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Results revealed that the market-bought sample from Oja-Oba contained Pb (2.2 mg/kg) and Cr (1.7 mg/kg) exceeding WHO/FAO permissible limits. The roadside-dried sample from Ido-Eruwa had the highest levels of Fe (37.2 mg/kg) and Cr (1.8 mg/kg), also surpassing safe thresholds. In contrast, the self-dried sample showed no detectable Pb, Cd, or Cr, indicating it was the safest. However, all samples had Selenium levels (1.3–3.3 mg/kg) above the recommended limit. The findings highlight the elevated health risks associated with cassava flour from market and roadside sources due to environmental contamination during processing. The study recommends the adoption of controlled drying practices, enhanced market processing standards, and stricter regulatory enforcement to ensure the safety of this widely consumed staple food